Pemanfaatan Aplikasi Pemesanan Makanan dan Dampaknya terhadap Kepuasan Pelayanan - Nasution, Deivy Zulyanti; Gantina, Devita; Fitriana, Rina (Jurnal Ilmiah Pariwisata; Vol 27 No 1 (2022): Jurnal Ilmiah Pariwisata, 2022)
The purpose of this study is to identify the effect of using the application in ordering food and drinks, how satisfied consumers are with ordering services through the application. This study uses descriptive qualitative research methods and looks at the relationship between the service quality perceived by consumers when they come directly to the restaurant and the service quality perceived by consumers when buying products. Using an application that is calculated using the T test. The sample in this study was taken by random sampling and involved 100 respondents. The test results can be seen that the p-value of the satisfaction variable is 0.055 which indicates a value greater than 0.05, so a decision can be made, meaning that the average satisfaction of respondents buying food directly is the same as the average satisfaction of respondents buying food through online applications. The results of this study indicate that the overall digital food ordering application does not have a negative effect on customer satisfaction, which means that there is the same satisfaction between delivery and direct orders. Keywords : Service Quality, Order Application, Come Directly